KETERBACAAN TEKS NARASI PADA BUKU TEMATIK KELAS III SEKOLAH DASAR - Visinsia Mila Anggraini (Universitas Katolik Musi Charitas, 2020)
Readability of a reading text can affect students' understanding of the reading text. Readability of a reading text can be measured one of them by using a fry chart. This study aims to describe the readability of narrative texts in the third grade thematic books of Elementary Schools. This research uses descriptive qualitative method. Data collection techniques used in this study were using purposive sampling technique. In this study, researchers only chose narrative text that has a number of words ? 100 words contained in the thematic books grade III Elementary School. After selecting the narrative text that has a number of words ? 100 words, 21 narrative texts were selected which were then analyzed for readability using a fry chart. Based on calculations from 21 narrative texts using fry charts, the results show that there are only 19% of narrative texts suitable for grade III elementary schools, 42.9% of narrative texts whose readings are suitable for grade levels above grade III elementary schools, and 38.1% of narrative texts which is declared invalid or unsuitable for use at any class level.